Use of Antenatal Perineal Massage on Primigravida to Reduce Perineal Trauma and Episiotomy during Vaginal Delivery at a Maternity Hospital in Saudi Arabia: A Mixed Method Inquiry - Mobarki, Misbah Ismail (British Journal of Healthcare and Medical Research, 2022)
The goal of this study is to determine the effectiveness of perineal massage in reducing cases of perineal and vaginal trauma. Perineal trauma refers to any injury to the perineum. To realize the goal, a sample of 100 primigravid women and 10 healthcare professionals will be used. The women will be divided into two groups, including the massage group and the control group. Women in the massage group will be subjected to perineal massage from the 34th week of their pregnancy. Women in the control group will not be subjected to these interventions. The relationship between perineal massage and the number of intact perineum following vaginal delivery will be determined. This will be used in determining whether perineal massage is an effective intervention in preventing perineal trauma. The healthcare professionals will be interviewed to provide more details about the ways in which perineal massage can be enhanced to reduce instances of perineal trauma during childbirth.